A highly efficient stratagem for protoplast isolation and genetic transformation in filamentous fungus Colletotrichum falcatum - Amalamol, Dharmaraj; Ashwin, N M R; Lakshana, Kana Valiyaveettil; Nirmal Bharathi, M; Ramesh Sundar, Amalraj; Sukumaran, Rajeev K; Malathi, Palaniyandi; Viswanathan, Rasappa (Folia microbiologica, 2022)
Red rot of sugarcane caused by the hemi-biotrophic fungal pathogen, Colletotrichum falcatum, is a major threat to sugarcane cultivation in many tropical countries such as India, Bangladesh, and Pakistan. With the accumulating information on pathogenicity determinants, namely, effectors and pathogen-associated molecular patterns (PAMPs) of C. falcatum, it is of paramount importance to decipher the functional role of these molecular players that may ultimately decide upon the outcome of sugarcane-C. falcatum interaction. Since C. falcatum is a multinucleated filamentous fungus, the conventional Agrobacterium-mediated transformation method could not be effectively utilized for targeted manipulation of genomic DNA. Hence, we developed a highly efficient protoplast-based transformation method for the virulent pathotype of C. falcatum - Cf671, which involves isolation of protoplast, polyethylene glycol (PEG)-mediated transformation, and regeneration of transformed protoplasts into hyphal colonies. In this study, germinating conidiospores of Cf671 were treated with different enzyme-osmoticum combinations, out of which 20 mg/mL lysing enzyme with 5 mg/mL β-glucanase in an osmoticum of 1.2 mol/L MgSO4 yielded maximum number of viable protoplasts. The resultant protoplasts were transformed with pAsp shuttle vector. Transformed protoplasts were regenerated into hyphal colonies under hygromycin selection and observed for GFP fluorescence. This protocol resulted in a transformation efficiency of > 130 transformants per μg of plasmid DNA. This method of transformation is rapid, simple, and more efficient for gene knockout, site-directed mutagenesis, ectopic expression, and other genetic functional characterization experiments in C. falcatum, even with large vectors (> 10 kb) and can also be applied for other filamentous fungi.
Keywords: Protoplasts; protoplasty; Colletotrichum; Transformation, Genetic; Saccharum; transformace genetická